Polityka proeksportowa w świetle wyzwań konkurencyjności strukturalnej - wybrane aspekty - Pluciński, Eugeniusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The main focus of this paper lies in interdependencies between structural competitiveness in global economic environment and pro-export policy. Fundamental thesis of this paper states that the base for pro-export policy nowadays should be most of all linked to the supply economic policy, unlike demand economic policy. The source of current export growth is subsidiary not complemenntary structure of economy. Economic complementary structure in globalized world is represented by a trade-off in the fields of technology and knowledge. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 282-293